Phenotypic evaluation of Festuca arundinacea Schreber populations naturalized in sub-humid semi-arid environments - Vega, Diamela Julieta (2021)
Tall fescue (Festuca arundinacea Schreber) is a temperate perennial forage important in livestock production systems due to its high yield in places with environmental and edaphic restrictions. The aim of this study was to evaluate the phenotypic performance of ten naturalized tall fescue populations in sub-humid semiarid environments of Argentina. The phenotypic traits plant height, crown diameter, number of tillers, and dry biomass production were estimated during three years. The data were examined through analysis of variance, correlation analysis, principal component analysis, and population × environment interaction analysis. The results suggest that there is high phenotypic variability among the ten naturalized tall fescue populations. A genotype × environment interaction was recorded for all traits (p < 0.05). The correlation analysis showed that the plant height trait could be useful to select indirectly higher plants in dry biomass production in individual and annual cuts. Populations 3243-645 and 3250-BAI stood out in the analyzed traits presenting stability throughout the years. The high phenotypic variability found is valuable to be explored in the future in the breeding program and to identify and select superior genotypes within populations.